A Brief Discussion of Vacuum Aided Closure Technique (International Journal of Food and Nutritional Sciences, 2022)
Background: The treatment doctors have always been concerned with how to manage wounds that are challenging to heal. The number of patients coming with wounds that are challenging to heal has dramatically increased. The management of these wounds has traditionally been done using conventional procedures, but not necessarily with the desired outcomes. Therefore, a newer, creative strategy that could be helpful in wounds that are difficult to heal and that produces results that are on par with or better than those produced by conventional techniques is what is required right now.